2011
DOI: 10.7439/ijbr.v2i8.127
|View full text |Cite
|
Sign up to set email alerts
|

Microneedles: An Effective Technique for Transdermal Drug Delivery

Abstract: Optimization of drug delivery through human skin is important in modern therapy. With limitations of oral drug delivery, pain and needle phobias associated with traditional injections drug delivery research has focused on transdermal delivery route. A new approach to transdermal delivery that acts as a bridge between the user friendless of patches and the broad effectiveness of hypodermic needles has recently received attention.by using needles of micron dimensions, termed microneedles, skin can be pierced to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 10 publications
3
2
0
Order By: Relevance
“…1). Similar changes in colour have also been observed in previous studies [32,33], thereby confirming the completion of reaction between the stem extracts and AgNO3. The AgNPs formation by reducing silver ions was investigated by UV-visible spectroscopy.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…1). Similar changes in colour have also been observed in previous studies [32,33], thereby confirming the completion of reaction between the stem extracts and AgNO3. The AgNPs formation by reducing silver ions was investigated by UV-visible spectroscopy.…”
Section: Resultssupporting
confidence: 90%
“…4a) showed that the particles are agglomerated and there was no clear shape. Similar result has been reported by Chitra and Annadurai [32]. The agglomeration might be due to the existence of large interaction between nanoparticles [41].…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…The application of nanoscale materials and structures, usually ranging from 1 to 100 nm is an emerging area of nanoscience and nanotechnology. Nanoscale materials are finding applications in biosensing, media recording, optics, catalysis, and environmental analysis and remediation [1].…”
Section: Introductionmentioning
confidence: 99%